2018
DOI: 10.1136/bmjopen-2017-020961
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of diabetes, pre-diabetes and associated risk factors: second National Diabetes Survey of Pakistan (NDSP), 2016–2017

Abstract: ObjectiveThe second National Diabetes Survey of Pakistan (second NDSP) was planned to ascertain the updated prevalence of diabetes, pre-diabetes and associated risk factors at the national and provincial levels.Research design and methodsThe survey was conducted by using multistage clustering technique in all four provinces of Pakistan from February 2016 to August 2017. An estimated sample size of 10 800 was calculated using probability sampling and multistage stratified sampling technique. Twenty-seven cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
193
6
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(215 citation statements)
references
References 23 publications
12
193
6
4
Order By: Relevance
“…A systematic review and meta-analysis of the global rural diabetes prevalence covering 1990-2012 showed that in lowand middle-income countries, the rural prevalence had increased from 1.8 to 7.5% (32). High prevalence of diabetes in rural areas is reported from other South Asian countries, such as Bangladesh (11), Pakistan (33), and Sri Lanka (13).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis of the global rural diabetes prevalence covering 1990-2012 showed that in lowand middle-income countries, the rural prevalence had increased from 1.8 to 7.5% (32). High prevalence of diabetes in rural areas is reported from other South Asian countries, such as Bangladesh (11), Pakistan (33), and Sri Lanka (13).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore speculate that the high load of Proteobacteria in Pakistani population is likely because of consuming too many carbohydrates without being calorie/exercise conscious. Indeed, a recent country-wide diabetes prevalence survey in Pakistan revealed that a staggering one-fourth of the Pakistani population over 20 is already or may become diabetic in the near-future [73]. These are issues of genuine concern that need to be addressed immediately at the national level.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of T2DM is exponentially increasing at high rate globally [5]. The survey conducted by the National Diabetes Survey of Pakistan (NDSP 2016-2017) showed that the incidence of diabetes is about 26.3% in Pakistan [6]. It is already known that vitamin D deficiency is linked with glucose intolerance, insulin resistance, metabolic syndrome, and increases the risk for diabetes [7].…”
Section: Introductionmentioning
confidence: 99%